Cognitive impairment and cognitive reserve, their correlations with behavioral features of patients with human immunodeficiency virus during hospitalization - O. V. Koltsova; G. Sh. Moshkova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2021)
The goal is to study the features of the cognitive reserve (CR) in HIV-infected patients admitted to the hospital, the relationship of CR with cognitive disorders, stress and coping strategies, taking into account the drug history.Materials and methods. The study was conducted in the hospital of the Saint Petersburg Center for the prevention and control of AIDS and infectious diseases in 2019. Methods were used: 1) The Cognitive Reserve Index questionnaire (CRIq); 2) Montreal Cognitive Assessment (MoCA); 3) «Methods of coping behavior» by R. Lazarus. 4) Modified Impact of Event Scale (IES-R); 5) The Somatic Symptom Disorder — B Criteria Scale (SSD-12).Results. The study involved 57 HIV-infected patients (43.9% — women). The median age was 39.6 years. The correlation analysis revealed a positive relationship between the KR index and the «non-professional activity» subscale (r = 0.847, p = 0.000), age (r = 0.299, p = 0.024) and MoCA indicators (r = 0.290, p = 0.029). Indicators of the KR subscale «professional activity» have a negative relationship with the indicators of coping strategies «distancing» (r = -0.379, p = 0.004), «self-control» (r = -0.355, p = 0.008), «positive revaluation» (r = -0.293, p = 0.030), «problem solving planning» (r = -0.283, p = 0.035). MoCA indicators in patients with HIV infection are associated with the CR «Education» subscale (r = 0.306, p = 0.021) and the General CR index (r = 0.290, p = 0.029). Obsessive feelings and thoughts related to the impact of HIV infection are more often experienced by patients who have never abused drugs and are involved in professional activities than by patients with experience of drug use.Conclusion. Cognitive impairment and cognitive reserve in HIV-infected patients admitted to the hospital of the AIDS Center are related to coping behavior.